Application of Tiny Flying Web Server for Delivery of Steganographic Images in Blankspot areas using Set Top Box (STB) Media: Rekayasa Keamanan Siber - muhammadabdurrahman; Gatut Yulisusianto; Yohanes Dwi Cahyono (Jurnal Telkommil, 2026)
This study aims to optimise the use of Set Top Box (STB)-based web servers in delivering steganographic images in blank spot areas. Steganography is a technique of hiding information in digital media so that its existence is difficult to detect, which plays an important role in communication security systems. The main problem faced is the difficulty of sending secret messages in areas that are not covered by the internet network. The methods used in this study include the development of a web server architecture that can interact with STBs, the installation of the Armbian operating system, and the implementation of web server services for the transmission of steganographic images. The results of the study show that an STB-based web server can function properly in transmitting steganographic images, where secret messages can be received and read correctly by the recipient. Thus, this study provides an innovative solution to improve connectivity and data security in blank spot areas, as well as contributing to the development of Internet of Things (IoT) technology and web server-based applications